PENGARUH THIN CAPITALIZATION, RETURN ON ASSET, DAN CORPORATE GOVERNANCE PADA PERUSAHAAN JAKARTA ISLAMI INDEX (JII) - Ismi, Fadhil; Linda, Linda (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study is to examine the effect of independent variables on tax avoidance of companies listed in Jakarta Islamic Index (JII) in the period of 2011 to 2015.Independent variables used in this study are thin capitalization, return on asset,and corporate governance. Corporate governance is proxied by public ownrship, the proportion of independent directors, audit quality and audit comittee. By using purposive sampling method, from 30 companies listed in JII, 15 companies are choosed as the sample of this study.The type of data used in this study is secondary data which is financial statement. Collecting data technique used in this study is documentary. Data is analyzed by statistical analysis using a multiple regression analysis. Then data is processed by IBM Statistical Package for Social Science (SPSS) 23th version program. The result of the study show that 16,5% dependent variable or tax avoidance can be explained by independent variables. Simultaneously the independent variables have effect n tax avoidance. Individually thin capitalization, return on asset and the proportion of independent directors have positive effect on tax avoidance and insignificant, audit comittee have negative effect on tax avoidance and insignificant.While public ownership have positif effect on tax avoidance and significant, and audit quality have negative effect on tax avoidance and significant.Keywords : Tax avoidance, thin capitalization, return on asset, corporate governance, public ownership, the proportion of independent directors, audit quality, audit comittee.